(untitled) (Horizontes de Enfermería, 2024)
Adaptability with psychomotor development includes four dimensions: biological, psychological, social, and gross motor development; for this reason, the present study explores the interrelation that exists between these elements and also makes a theoretical approach to the processes as mentioned earlier, starting from the perspective of different authors and giving particular importance to those historical milestones related to the research problem. For this purpose, descriptive research was carried out using qualitative variables, thanks to which those specific needs associated with the acquisition or manifestation of the skills of interest were identified; in addition, a scientific observation technique was used, thanks to which the most recurrent facts for certain specific needs were appreciated. In addition, the Denver Test was applied to the population under study, and a psychomotor interview was conducted in which the parents were consulted. The results allowed us to appreciate that there is a relationship between adaptability and psychomotor development. After applying the instrument, infants do not experience severe delays, that is, maladjustment. In cases where maladjustment results are recorded, there is a link between the socioeconomic characteristics of the family and the level of relationship that parents have with their children. Through the participation of the promoters-coordinators and the assertive communication of the parents, the problems that could trigger the children can be detected in time, both in their development and adaptability and thus, early warning signs can be identified.